Interview of Herbert Levack by Dian O. Belanger - Levack, Herbert (Byrd Polar Research Center Archival Program, 2009)
The Antarctic Deep Freeze oral history project was funded by a grant from the National Science Foundation and supported by the Antarctic Deep Freeze Association. The original paper copies and unaltered tapes have been deposited in the library of the National Science Foundation. Herb Levack's Air Force troop carrier squadron was chosen for air support of the inland IGY stations beginning in Deep Freeze II because its C-124s were the largest and most suitable cargo aircraft at the time, and his unit had had experience landing materials in the Arctic for the DEW Line. Levack, a pilot and the operations officer, discussed loading and flying the planes to the Pole (and Byrd), the mechanics and timing of the low-altitude drops, and having to retreat to New Zealand when the ice runway deteriorated until colder weather and ice repair made the airstrip safe again. In Deep Freeze IV, four C-124s returning from Pole and Byrd made safe emergency landings at Hallett when weather turned foul at McMurdo, but just a week later a similar plane coming from Christchurch smashed into a nearby mountain with six fatalities. National Science Foundation Antarctic Deep Freeze Association